Produção de conhecimento sobre formação continuada de professores da educação infantil: estudo com base nos PPGs da região nordeste do Brasil - Mota, Déborah Helany Pilar Castro Costa (Universidade do Vale do Rio dos Sinos, 2021)
This essay analyses academic studies, dissertations and theses on the Continuous Professional Development for teachers in the Early Childhood Education carried out in PPGs in the northeast region of Brazil, from 2010 to 2019, highlighting their problems regarding research and their theoretical-methodological references. So, the implantation/ extension of the PPGs in education from the northeast region were contextualized; dissertations and theses carried out in those PPGs regarding the continuous professional development for early childhood education teachers were selected, an analytical balance from those dissertations and theses was elaborated. As theoretical-methodological procedures, a qualitative approach was used through bibliographical research named “State of the Art” based on Romanowski and Ens (2006), and the “production of meanings”, supported on Aguiar and Ozella (2013) was used. As results, it was observed that the papers analyzed show that the continuous professional development air an academic approach, made by technical and theoretical contents that aim filling in the gaps in the teachers’ early formation and didactic sequences to be developed with children aged 0 to 5. The papers also show the need of those formation to be connected to the pedagogical practice, enabling a reflexive formation that mobilizes collective moments of interaction, experience shares, desires for change, professionalization and qualification of the pedagogical practice, thus impacting the children’s teaching and learning process.
Keywords: Estado da arte; Formação continuada; Educação infantil; PPGs em Educação da região nordeste; State of art; Continuous professional development; Early childhood education; PPGs in education in the northeast region; ACCNPQ::Ciências Humanas::Educação